Pengaruh Motivasi, Lingkungan Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Astra International Tbk-Auto2000 Cabang Balikpapan Sudirman: Pengaruh Motivasi, Lingkungan Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Astra International Tbk-Auto2000 Cabang Balikpapan Sudirman - Nita Andryani; Ariani, Misna; Yuliani, Tutik (Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to analyze the influence of motivation, work environment, and work discipline on the performance of employees at PT. Astra International Tbk-Auto2000 Balikpapan Sudirman. The research design employed is quantitative research. The sample size in this study consists of 68 permanent employees. The sampling technique used is purposive sampling. The software utilized for this research is Smart PLS. The results of the study indicate that motivation has a significant effect on employee performance. The work environment also has a significant impact on employee performance. Additionally, work discipline influences employee performance.